Simulation study of cinema evacuation through cellular automata and agent based model - Yong, Shihao (2017)
Over the years, movies have become a widely known entertainment for all ages. Most people would often spend their weekends with their spouse or children in cinema watching their favourite blockbuster or family movies. However as due to the frequent terrorist attacks and risk of fire, there have been a growing concern in the safety of these movie-goers when these emergency situation occurs. This is because the Cinema hall is always dark with only narrow gangway and aisles for movement. This often results in slow evacuation during an event of a fire or even terrorist act. Confusion and even panic may also occur during the evacuation which may even cause causalities. Over the years, many researches have been done on the evacuation of enclosed places that are vulnerable to these events. Out of the many simulation models, 2 models have been used commonly in research papers and software for evacuation. They are the Cellular Automata Model and the Agent Based Model. This report aims to use these 2 models in simulating an evacuation of a typical cinema. Through these 2 models, the report aims to observed the places where slow movement of people such as congestion occurs during the evacuation process. In order to simulate a more realistic environment, the layout for the simulation model is a modified model of an actual cinema hall. Human psychology and behaviour are also considered when simulating the evacuation process through both models. For the simulation through the agent based model, timings required for all agents to escape from the cinema are also recorded. Solutions are also suggested in help reduce congestion in both models. These solutions include placing of front exits closer to the aisles, placing of additional aisles at both sides of theatre, changing the seats of cinema to allow foldable seat back and video about evacuation routes and safety before movie. Some of the solutions such as placing of front exits closer to the aisles and placing of additional aisles at both sides of theatre are tested out through the agent based model through the use of the program Oasys Massmotion to determine if these solutions are efficient in reducing the total